Comparing the Effects of Progressive Muscle Relaxation and Guided Imagery on sleep quality in primigravida women referring to Mashhad health care centers-1393 - Nahid Golmakani; Farnaz Sadat Seyed Ahmadi Nejad; Mohammad Taghi Shakeri; Negar Asghari Pour (Mashhad University of Medical Sciences, 2015)
Background & aim: Decreased sleep quality is a common complaint during pregnancy. Relaxation is one of the non-pharmaceutical treatments for sleep disorders. Different techniques could have different impacts on various biological and mental stressors. Therefore, this study aimed to compare the effects of progressive muscle relaxation and guided imagery on the sleep quality of primigravida women. Methods:This three-group clinical trial was conducted on 100 primigravida women, referring to Mashhad health care centers in 2014. All women, who met the inclusion criteria, were randomly assigned to three groups: progressive muscle relaxation, guided imagery, and control groups. The intervention groups performed the exercises twice a day for a period of four weeks at home after two sessions of relaxation training (held during two weeks). Then, the quality of sleep was measured using Pittsburgh Sleep Quality Index. For data analysis, ANOVA, Kruskal-Wallis, paired t-test, and post-hoc test were performed, using SPSS version 11.5. Results: The total score of sleep quality and its components (except use of sleep medication) was significantly lower after the intervention, compared to the pre-intervention period in progressive muscle relaxation and guided imagery groups (P